Cardiovascular Fitness Profile of Sleman Regency PLAPD Volleyball Athletes - Syamsuryadin, Syamsuryadin; Wahyuti, Sri Ayu; Prasetyo , Heru (Yayasan Insan Mulia Bima, 2024)
This study uses quantitative methods with descriptive observational research design. Research is used to see a picture of the phenomenon, the description of activities is carried out systematically and emphasises more on factual data than inference (Kanji, Nursalam, Nawir, and Suardi., 2019). This research only makes observations (observations) on the research subject without intervening in the research subject. The subjects of this study used Sleman Regency PLAPD volleyball athletes totalling 40 athletes consisting of 20 boys and 20 girls. The cardiovascular fitness test using the MFT test was carried out on Saturday, 18 November 2023 at Gor Pangukan, Sleman, Yogyakarta Special Region. The data analysis technique used in this study is univariate analysis. Univariate analysis is a way of analysing a single variable (Aquarista and Hadi, 2017). Univariate analysis is used to explain or describe the characteristics of each research variable (Gilang, Notoatmodjo, and Rakhmawatie 2012). The form of univariate analysis depends on the type of data. Numeric data used mean and median values. This analysis only produces frequency distribution and percentage of each variable. The type of data in this assessment is numerical data (quantitative) and the values used are mean median and standard deviation. Then the results are analysed descriptively in the form of frequency and percentage. From the findings that have been carried out, it can be concluded that the level of cardiovascular fitness of Sleman Regency PLAPD volleyball athletes, both male and female, is in the deficient category.